The Role of Good Corporate Governance in Moderating the Financial Performance of Sharia Banks: A Case Study at Bank Muamalat Indonesia - Nur Haida; Yeni Nurkhasanah (Transpublika Publisher, 2025)
Fluctuating financial performance of PT Bank Muamalat Indonesia, Tbk., particularly its profitability, amid varying levels of operating expenses, non-performing financing, and financing distribution constitutes the core issue of this research. This research aims to examine how operating expenses, non-performing financing, and financing distribution affect profitability, as well as to assess the extent to which good corporate governance (GCG) ratings moderate each of these relationships in influencing the financial performance of PT Bank Muamalat Indonesia, Tbk. over the 2007-2023 period. A quantitative approach with an associative design was employed. Data were gathered through document collection techniques from the company’s website, making them secondary in nature. The population consisted of Bank Muamalat’s annual reports, and a purposive sampling method was used to include all available data from 2007 to 2023. Analytical procedures involved interpolation, descriptive statistics, stationarity testing, and classical assumption tests. Subsequently, multiple linear regression was conducted using a Goodness of Fit model, followed by Moderated Regression Analysis (MRA). The findings indicate that BOPO has a significant negative effect on ROA, while gross NPF and FDR each show insignificant negative effects on ROA. Furthermore, the MRA results reveal that GCG does not moderate the partial relationships between BOPO, gross NPF, or FDR and ROA.